Konsep Jñāna dalam Bhagavad Gītā - Ida Bagus Subrahmaniam Saitya; Adi Suryana (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
In the Bhagavad-gītā there are several concepts that explain the path to Brahman one of which is the Jñāna path. This is certainly interesting if studied in depth about the point of view of this path of consciousness or knowledge. That is why this article attempts to discuss the concept of Jñāna in the Bhagavad-gītā. This study aims to find out (1) Bhagavad-gītā's Statement About Jñāna; (2) The process of the tmā to Brahman using Jñāna; (3) Jñāna as a means of liberation. The theories used to analyze the problem are: Hermeneutics theory from Hans Georg Gadamer, and Value theory from Tarigan. The subject of this research is Bhagavad-gītā. Data collection techniques are literature study and documentation study. The collected data were analyzed by qualitative descriptive analysis method with steps of data collection, data reduction, data presentation and conclusion drawing. The results show (1) Bhagavad-gītā's statement about Jñāna, namely: Jñāna as a human tool to achieve divine consciousness, Jñāna has the most exalted position of any concept. (2) The process of the tmā to Brahman using Jñāna namely: Suddhā Vikalpa, Bhavana, Suddhā Widya, and uniting with Brahman. (3) Jñāna as a means of liberation, namely: Srawanam, Manana, Nididhyasana, Nirvikalpa. From this research it can be understood the main teachings of Jñāna contained in the Bhagavad-gītā. So this article concludes that Jñāna is one of the most basic and sublime concepts in the Bhagavad-gītā.